2017
DOI: 10.12968/bjom.2017.25.9.572
|View full text |Cite
|
Sign up to set email alerts
|

Male child preference: Is it a risk factor for antenatal depression among Iranian women?

Abstract: Background Male child preference is a phenomenon in decline in Asian women. However, it continues to exert hidden pressure on childbearing women in developing countries to dispose them to depression during pregnancy. Aims This study assessed the prevalence of antenatal depression and hypothesised that maternal perception of a family's male child preference was an independent risk factor for depression. Methods This was a cross-sectional study of 780 pregnant women who attended routine antenatal appointments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…None of the participants in any group stated that they wished for a daughter, which was also seen in another study done in Iran (Murphy et al, 2011). According to some, daughters are desired in societies that usually prefer sons because daughters can help in household work (Rouhi et al, 2017). The percentage of housewives who preferred to have more than four sons was similar to those housewives who preferred to have only three or four.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…None of the participants in any group stated that they wished for a daughter, which was also seen in another study done in Iran (Murphy et al, 2011). According to some, daughters are desired in societies that usually prefer sons because daughters can help in household work (Rouhi et al, 2017). The percentage of housewives who preferred to have more than four sons was similar to those housewives who preferred to have only three or four.…”
Section: Discussionsupporting
confidence: 50%
“…A country like China, which is suffering from the effects of an ancient and entrenched cultural preference for sons, has taken steps via policymaking and awareness raising to minimize it (Sadaqat et al, 2011). South Asian countries are suffering from a preference for sons, adversely affecting women's nutritional, educational, and healthcare needs, and making them even more vulnerable and weak in patriarchal society (Hank, 2007;Rouhi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Gender preference for the child appears to be a relatively under-researched determinant in relation to antenatal depression/anxiety, as highlighted by the small number of studies included in this review which addressed it, despite it being a common societal issue within these South Asian countries [ 62 ]. The significant association between preferring a male child and antenatal depression/anxiety found in this review is reflected in observational studies conducted in China [ 63 ] and Iran [ 64 ]. Male children are considered a blessing as they carry the family name and can provide for their parents in old age, whereas female children are viewed as a burden for the family [ 61 ].…”
Section: Discussionmentioning
confidence: 74%
“…The husband's gender preference for the baby as perceived by the pregnant woman has not been widely investigated in Bangladesh. A study of pregnant women in Iran [30] found that the husband's preference for a male child is significantly associated with antenatal depression in women. Similarly, a study of pregnant women in China [31] found that no gender preference in the spouse was associated with a significant reduction in persistent depression.…”
Section: Key Findingsmentioning
confidence: 99%